Case Report Study of an Integrated Treatment Approach in Critical Case of Covid-19 Patient (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The world has seen various variants of coronavirus and attempting all the feasible options to combat this pandemic situation. By far, vaccination is the most remarkable approach in controlling the Pandemic. India is fighting against the delta variant of the second wave COVID-19. Meanwhile, World Health Organization has already warned about the initial stages of the third wave in all countries. Therefore, on considering the variants of coronavirus, no standard option of care is available to date. In this article, we present a case study on the clinical outcome of the integrated treatment approach in COVID-19 patients suffering from critical conditions. The patient with a history of coronavirus was advised of strict home quarantine and standard treatment of care for 14 days. She was brought to the COVID-19 healthcare center in an unconscious state by her family. On examination, she had a 79% oxygen saturation, heart rate 88 beats/minute and her laboratory findings: CRP 37.3(mg/dL), ESR 84(mm/hour), D-dimer 793(ng/mL), and RBS 158 mg/d. After receiving consent from her family members, we initiated the integrated treatment approach. It includes T-AYU-HM Premium 600mg, is a herbo-mineral formulation, and Acupen 600 mg thrice a day with modern medicines. By adhering to the treatment, she recovered completely within a one-month duration. Her HRCT report showed a significant reduction in lung involvement with ill-defined low-density ground-glass opacities and atelectatic bands in both lungs. The patient's vitals and laboratory parameters presented striking improvement. This case study provides information about the effect of the integrated treatment approach in critical COVID-19 cases.